Mass Customisation in a Service Context An After Sales Service Case Study in Chile - Armas, Felipe (2010)
Mass customisation is a relatively new business strategy that attempts to combine the efficiency of mass production with the level of individualisation of a customised product. At first impression this ideal seems contradictory, but the truth is that its success has already been proven in several occasions. Now a day’s mass customised products can be found almost everywhere, and studies of how the operations that build these products work have become numerous too. But it has been noticed that the same has not happened in the case of services, even if some of the greatest experts on the topic assure that its implementation in this context should be even easier and with greater benefits. As it appears to be yet lots to discover about the implementation of mass customisation for services, this paper will discuss the reasons why to implement the strategy, along with its advantages and limitations. The case study will be done upon the after sales service of a construction company in Chile, who’s demand for high quality tailor-made solutions has increase significant over the last year due to post earthquake situation. Finally the results of the case study will be presented as key findings and the answers to the research questions.